2022
DOI: 10.3390/polym14101992
|View full text |Cite
|
Sign up to set email alerts
|

3D Printing of Stretchable, Adhesive and Conductive Ti3C2Tx-Polyacrylic Acid Hydrogels

Abstract: Stretchable, adhesive, and conductive hydrogels have been regarded as ideal interfacial materials for seamless and biocompatible integration with the human body. However, existing hydrogels can rarely achieve good mechanical, electrical, and adhesive properties simultaneously, as well as limited patterning/manufacturing techniques posing severe challenges to bioelectronic research and their practical applications. Herein, we develop a stretchable, adhesive, and conductive Ti3C2Tx-polyacrylic acid hydrogel by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…The AC particles settle by gravity in the solution, and the viscosity of the PVA solution prevents the settling rate of the AC particles until the AC particles maintain equilibrium. The rheological characterization of the PVA-AC conductive hydrogel inks demonstrates that the viscous PVA solution facilitates the conductive AC to disperse ( Figure 1 b) [ 26 , 27 , 28 ]. The continuous conductive network eliminates the tunneling effect between the conductive particles and the substrate material, effectively minimizing hysteresis during the stretching process.…”
Section: Resultsmentioning
confidence: 99%
“…The AC particles settle by gravity in the solution, and the viscosity of the PVA solution prevents the settling rate of the AC particles until the AC particles maintain equilibrium. The rheological characterization of the PVA-AC conductive hydrogel inks demonstrates that the viscous PVA solution facilitates the conductive AC to disperse ( Figure 1 b) [ 26 , 27 , 28 ]. The continuous conductive network eliminates the tunneling effect between the conductive particles and the substrate material, effectively minimizing hysteresis during the stretching process.…”
Section: Resultsmentioning
confidence: 99%
“…To avoid the functionalization through bio-active molecules, increasing interest in the synthesis of conductive polymers that are also printable—such as poly(3,4-ethylenedioxythiophene): polystyrene sulfonate (PEDOT:PSS) [ 109 ], which can be conveniently enriched by poly(vinyl alcohol) (PVA) forming a hydrogel strain sensor [ 110 ]—has been conveyed. Conductive hydrogels may become ideal interfaces with the human body, but rarely simultaneously possess the satisfying electrical, mechanical, and adhesive properties shown by the Ti3C2Tx-polyacrylic acid hydrogel that can be printed into complex geometries with high resolution [ 111 ].…”
Section: Biomimetic Scaffolds To Reproduce the Micro-environment Of Pdlmentioning
confidence: 99%
“…The colorimetric appearance of the hydrogel changed with pH, and the absorption peak positions were correlated to the pH ranges. However, these studies [ 2 , 10 , 11 , 12 , 13 , 14 ] did not disclose the drainage capability of the dyes from the hydrogel matrix. This is an important aspect because the entrapment only occurred on the surface of the wound dressing, which causes dye leakage when they come in contact with excess exudates.…”
Section: Introductionmentioning
confidence: 99%
“…They snapped the printed hydrogel and reattached it to the body’s original form to test the PAA’s adhesion capability. Zhao et al [ 12 ] additively manufactured a stretchable and highly adhesive Ti 3 C 2 Tx-PAA hydrogel using ink writing 3D printing. They demonstrated the adhesion capability on various materials, such as glass, metal, PTFE, and pigskin, with different concentrations of Ti 3 C 2 Tx and PAA, and it was found that increasing the concentration of PAA enhanced the adhesion strength significantly.…”
Section: Introductionmentioning
confidence: 99%